Polymerization of Acrylamide in Water (Journal of the College of Basic Education, 2022)
An experimental investigation of kinetics of the solution free radical homopolymerization of acrylamide initiated with potassium per sulfate (PS) was conducted at 70C. The overall activation energy of homopolymerization was determined to be ( 24.65 ) kJ mol-1. The effects of initiator and monomer concentration on the rate of homopolymerization were studied over a wide range using the well-known conversion vs. time approach in dilute solution. Under the condition of our work the overall rate of polymerization was proportional to (initiator concentration)1/2however, in contrast to the classical kinetic picture, it is not directly proportional to the monomer concentration .Key words: Acrylamide, radical polymerization, kinetic aspects